Teenage gestation relapse: experienced potentialities and fragilities (Research, Society and Development, 2020)
Adolescent pregnancy is still a period that needs more follow-up, both in the family nucleus and at school and with health professionals. The objective of this research was to construct an informative primer, emphasizing the care to prevent recidivism of gestation in adolescence. An action research was carried out, with qualitative approach used the methodology of research group care. The Human Care Theory was developed by Margaret Jean Watson as part of the Caritas Clinical Process. This process is used to instrumentalize and assist nurses in conducting group care. From the process of analysis of the results obtained in the meetings emerged four categories: "Fragilities involving the environment of pregnancy in adolescence"; "Lack of Family Dialogue"; "School Abandonment after the Birth of the Son"; and "Gestational Recidivism". After analyzing the results, an informative booklet was constructed, with the main speeches of the adolescents who emphasized having a hopeful look for the future, and that dialogue is fundamental.